Prognostic Factors for Survival in Patients with Gastric Cancer Treated at Two Public Health Institutions in Mexico - Trujillo-Rivera, Alejandro; Sampieri, Clara Luz; Morales, Linda; Montoya, Alejandra; Lamadrid-Figueroa, Héctor (Asian Pacific Journal of Cancer Care, 2021)
Objective: To analyze the clinical records of patients with gastric adenocarcinoma, treated at two different public health institutions in Mexico to determine survival rates. Methods: Cox proportional-hazards model was fitted to identify the factors involved in survival of patients. Result: The results show that subjects aged 41 to 50 years of age had a 56% lower risk of death from gastric cancer compared to those <40 years of age. Asthenia and/or adynamia, weight loss and leukocytosis increased the risk of dying. The incidence of melena was found to be a protective factor for mortality. Conclusion: At age <40 years, symptoms such as asthenia, adynamia and weight loss and leukocytosis are poor prognosis predictors in patients with gastric cancer. Melena seems to be a protective sign of gastric cancer mortality in Mexico. Given the low 5-year survival rate in patients with gastric cancer, further studies are necessary to explore the factors associated with survival to contribute to effective intervention.